2018
DOI: 10.7554/elife.31377
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Toll-like receptors nucleates assembly of the MyDDosome signaling hub

Abstract: Infection and tissue damage induces assembly of supramolecular organizing centres (SMOCs)), such as the Toll-like receptor (TLR) MyDDosome, to co-ordinate inflammatory signaling. SMOC assembly is thought to drive digital all-or-none responses, yet TLR activation by diverse microbes induces anything from mild to severe inflammation. Using single-molecule imaging of TLR4-MyDDosome signaling in living macrophages, we find that MyDDosomes assemble within minutes of TLR4 stimulation. TLR4/MD2 activation leads only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
115
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(124 citation statements)
references
References 42 publications
9
115
0
Order By: Relevance
“…This data complements the previous Myddosome data that shows assemblies of 6-8 MyD88 DDs 23 . Our results are also consistent with the recent single molecule fluorescence microscopy studies by Latty et al 23 demonstrating the formation of both smaller (6 MyD88 complexes approximately) and 'super' Myddosomes at the cell surface. Overall, the different domains exhibit unique oligomerisation propensities, with both domains presence necessary but not sufficient for the formation of polymers.…”
Section: At Low Concentrations Both the Tir And Death Domains Are Resupporting
confidence: 93%
See 1 more Smart Citation
“…This data complements the previous Myddosome data that shows assemblies of 6-8 MyD88 DDs 23 . Our results are also consistent with the recent single molecule fluorescence microscopy studies by Latty et al 23 demonstrating the formation of both smaller (6 MyD88 complexes approximately) and 'super' Myddosomes at the cell surface. Overall, the different domains exhibit unique oligomerisation propensities, with both domains presence necessary but not sufficient for the formation of polymers.…”
Section: At Low Concentrations Both the Tir And Death Domains Are Resupporting
confidence: 93%
“…For many years, TIR domain associations, which are weak and transient, have been seen to contribute little to the oligomerisation status of signalling proteins 27,28 . However, the recent cryoEM structure of Mal TIR domain in filamentous form, as well as novel studies 12 ,demonstrated that upon specific ligand binding TIR-containing proteins cooperatively assemble into large multiprotein complexes 12,23 . The TIR domain of MyD88 was also demonstrated to polymerise but only upon seeding by Mal filaments.…”
Section: Full-length Myd88 Biophysical Behaviour and Its Link To Signmentioning
confidence: 99%
“…Despite the well-known function of TLR4 as an inflammatory player, it is not fully understood how TLR4, especially its intracellular TIR domain, forms a homo-oligomer upon LPS binding to the extracellular domain (17,30). It has been reported that TLR4 could exist as preformed dimers in the absence of ligand and that complete activation of TLR4 needs not only ligand binding but also apposition of the TIR domains (31). It has been long thought that additional factors proximal to the plasma membrane may facilitate the homoassociation of TLR4 during its activation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the IFN‐γ receptor complex joins other innate receptors that form higher order complexes of hexamers, dodecamers or more (e.g. the GM CSFR and TLR4) …”
mentioning
confidence: 99%
“…the GM CSFR and TLR4). 15,16 Mendoza et al used the structure to investigate the IFNGR2 mutation T168N that is associated with the lack of IFN-c responsiveness resulting in a predisposition to mycobacterial infection. 1 The asparagine in the IFNGR2T168N mutant sits in the interface of IFNGR2 with the IFNg/IFNGR1 complex.…”
mentioning
confidence: 99%